Dictionary Filter Java Banten in Instagram Application As A Solution to Maintenance and Value of Planting Local Wisdom Banten - M. Fiqri Berlian; Siti Padia Hijriyana; Diana Mutiarani (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
Banten Javanese language is one of the features of the word from the Sultanate of Banten, which is still in use by the community today. After the fall of Banten's Sultanate, this style of language is always inherent in some towns, and its usage almost spread in several major cities in Banten. Besides being used to show the existence of regional and Javanese language communication tools, Banten contains a sublime moral value that can reflect the region and can deliver character-building owned by the next generation, in today's flow of modernization and globalization. In the current digitalization era, information and communication technology has entered all sectors of life. When it found in many dictionary digital forms, use can be via a smartphone or through a computer. The purpose of preserving the Banten regional language, namely Java Banten, is to maintain its existence. One of the maintenance efforts that can do is by using a digital dictionary filter contained in the instagram application.